A multi-body model for comparative study of cervical traction simulation – development, improvement and validation. Issue 8 (11th June 2019) - Wong, Lawrence K. F.; Luo, Zhiwei; Kurusu, Nobuyuki; Fujino, Keiji
Abstract: A computer simulation model was developed to study the dynamic behavior of the cervical spine during cervical traction therapy in inclined and sitting traction positions. The model improved upon an old model with additional components to represent the behavior of the intervertebral discs and the posterior ligaments. The simulation result of the new model was compared against the cervical traction data from a radiographic experiment in both positions. The simulation results of the old model and new model were compared to illustrate the improvement. Using the new model, we compared the timing response of cervical traction in the inclined and sitting positions.